2018
DOI: 10.1063/1.5052708
|View full text |Cite
|
Sign up to set email alerts
|

Stress relief by annealing under external stress in Fe-based metallic glasses

Abstract: The effects of stress relief on the magnetic characteristics of Fe-based metallic glass (MG) ribbons are investigated under external stress through various annealing treatments. We found that long-time annealing treatments benefit for making softer magnetic MGs under applied bending stress. We show that the irreversible domain wall movement region and the irreversible domain wall rotation region in the M-H curve represent the stress relief, which can be well reflected by the demagnified magnetic anisotropy. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…The σ is calculated according to equation (3), and we can clearly see that the larger Δr = r i0 -r i1 is, the larger the bending stress σ of the nanocrystalline core in the bending direction. This phenomenon is consistent with previous reports in the literature [11,15].…”
Section: Sample Preparationsupporting
confidence: 94%
See 3 more Smart Citations
“…The σ is calculated according to equation (3), and we can clearly see that the larger Δr = r i0 -r i1 is, the larger the bending stress σ of the nanocrystalline core in the bending direction. This phenomenon is consistent with previous reports in the literature [11,15].…”
Section: Sample Preparationsupporting
confidence: 94%
“…Previous studies have shown that magnetostriction, stress, and temperature may be the origin of magnetic anisotropy [15,26,27]. E k (magnetic anisotropy energy) is defined as the energy required to reach magnetic saturation from a demagnetized state, as shown in equation (11) and the figure 4(a) [11].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The high stress levels during the extremely cold process of quenching result in magnetic domains with irregular shapes, varying widths, disordered orientations and the presence of fine fingerprint domains. Residual stress has a detrimental effect on magnetic properties, and annealing has been proven to be effective in relieving internal stress and enhancing the magnetic properties of the ribbons [ 23 ]. Annealing induces structural relaxation and the release of internal stress in the amorphous strip, causing the magnetic domains within the strip to align along the direction of the easily magnetized axis, which is parallel to the strip’s length.…”
Section: Resultsmentioning
confidence: 99%